Mechanistic diversity between nitrate and nitrite on biocorrosion of X80 pipeline steel caused by Desulfovibrio desulfurican and Pseudomonas stutzeri. (October 2022) - Fu, Qi; Xu, Jin; Wei, Boxin; Qin, Qingyu; Bai, Yunlong; Yu, Changkun; Sun, Cheng
Abstract: The effects of Desulfovibrio desulfurican (D. desulfurican) and Pseudomonas stutzeri (P. stutzeri) on the biocorrosion of X80 pipeline steel for different nitrate and nitrite concentrations were studied. After treatment with nitrate and nitrite, the number of D. desulfurican cells decreased rapidly, and the inhibition effect of nitrite was more significant. However, the samples treated with nitrate suffered serious pitting corrosion, while the surface of the samples treated with nitrite formed γ-Fe2 O3 passivation films, which hindered the formation of erosion pits. Furthermore, nitrite also resulted in a significant decrease in the content of FeS, which was helpful to reduce corrosion. Highlights: Nitrate weakens SRB corrosion but enhances NRB corrosion. Nitrite can passivate the steel surface to prevent corrosion. The production of sulfide can be greatly inhibited by nitrite. Nitrite treatment of SRB corrosion is superior to nitrate.